Implementasi Model PBL Melalui Pendekatan Saintifik Dalam Meningkatkan Hasil Belajar - Yotam Kasene (Peneliti.net, 2023)
In the world of education, the development and introduction of the natural environment is indispensable. Because through natural education humans can recognize and observe the processes that occur in nature. The introduction of nature in elementary schools is taught through learning by studying Natural Sciences (IPA). According to Sitiatava (2012: 51) in Syafriana (2017)